Economic evaluation of installation of standalone wind farm and wind + CAES system for the new regulating tariffs for renewables in Egypt. (September 2018) - Ramadan, Omar; Omer, Siddig; Ding, Yate; Jarimi, Hasila; Chen, Xiangjie; Riffat, Saffa
Highlights: Adding CAES to wind farm was economically investigated for Egyptian grid. Economic investigation was carried out based on calculation of net present value. Egyptian tariff for renewables was used to perform numerical analysis using MATLAB. Operation of CAES system was compared for load-levelling and profit maximization. Wind + CAES ($306 m) yield higher NPV compared to wind alone ($207 m), payback of 18 years. Abstract: Compressed Air Energy Storage (CAES) is widely recognized as a viable solution for large-scale grid integrated renewable energy systems in terms of load levelling to solve/minimize the intermittency effect of renewable energy systems especially with increased penetration of renewables to the grid. This study assesses the economic value of adding compressed air energy storage (CAES) plant to a renewable energy system and how this impacts the overall financial appeal of the system at hand, taking Egyptian grid as a case in point. Numerical modelling using MATLAB was performed to analyse the benefits of adding a CAES system to planned wind farms in Egypt by 2020 for both load-levelling as well as optimizing economic benefit. The results show that the addition of a CAES system would increase the profitability for the new Tariff for wind systems set by the Egyptian government with a NPV of $306 m compared to a NPV of $207 m of a stand-alone wind system at the end of 25 years of operation. Also, the economic benefits increase if the government provides subsidies for new installations of renewable energy systems, or by lowering the interest rates.